Pengembangan Media Pembelajaran Ekonomi dengan Pendekatan Contextual Teaching and Learning Berbasis Google Sites di Moderasi Literasi Digital untuk Meningkatkan Hasil Belajar Siswa Kelas XI IPS SMA Swasta ST Ignasius Medan T.P 2023/2024 - Ginting, Esti Julianita; Nugrahadi, Eko Wahyu; Siregar, Zulkarnain (Cetta: Jurnal Ilmu Pendidikan, 2024)
The limited digital media available is one of the obstacles in maximizing the learning process. Based on initial observations, researchers found that there were problems with the academic performance of Medan High School Class This research aims to develop media in digital form based on CTL with digital literacy level as a moderating variable to improve economic learning outcomes at Santo Ignasius High School Medan Class XI IPS 1. This research uses a more general learning design model, namely the ADDIE model. This development model has five stages, namely: Analysis, Design, Development, Implementation and Evaluation (ADDIE). This research was carried out at SMA Santo Ignasius Medan with a population of 36 students. Based on the feasibility validation test for CTL-based digital media carried out by experts, the average result was 86.13% with a very feasible category. The post-test score obtained by the experimental class which was processed with the developed CTL-based digital media was an average of 89.59, while the post-test score for the control class obtained a school average of 86.56. Therefore, it can be concluded that the digital media developed based on CTL is effectively applied to improve the learning outcomes of class XI IPS 1 SMA Santo Ignasius Medan to be applied to classroom learning.